Stazioni GNSS Permanenti e misure locali del livello del mare Il caso della Stazione Mareografica Integrata di Porto Garibaldi - Perfetti, Nicola (GEOmedia, 2014)
The article deals with the problem of correct estimation of the rate of rise of the mean sea level punctual. For a single marigraph the propo sed solution consists in co rrecting the measurement of po tential eustatism, which may be inco rrect due to movement of the tide gauge due to both loc al and territorial effects, using the estimate of the po ssible value of vertical velocity of the structure. The proposed solution co nsists in mo unting on a tide gauge, a permanent GNSS station and com bining the time series of the tide gauge with those of the GNSS station thereby obtaining the estimate of the real trend of the average sea level.